2015
DOI: 10.3389/fpls.2015.00340
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid modulates arsenic toxicity by reducing its root to shoot translocation in rice (Oryza sativa L.)

Abstract: Arsenic (As) is posing serious health concerns in South East Asia where rice, an efficient accumulator of As, is prominent crop. Salicylic acid (SA) is an important signaling molecule and plays a crucial role in resistance against biotic and abiotic stress in plants. In present study, ameliorative effect of SA against arsenate (AsV) toxicity has been investigated in rice (Oryza sativa L.). Arsenate stress hampered the plant growth in terms of root, shoots length, and biomass as well as it enhanced the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 68 publications
10
54
1
2
Order By: Relevance
“…While exogenous SA counteracted the As-induced increase in ROS levels (Table 2). Our findings are in line with that of Odjegba (2012) and Singh et al (2015a) in Arabidopsis thaliana and Oryza sativa L. SA mediated lowering in ROS indicates a protective role against As-stress.…”
Section: Contamination Of As In Plants Has Closely Been Linkedsupporting
confidence: 92%
See 2 more Smart Citations
“…While exogenous SA counteracted the As-induced increase in ROS levels (Table 2). Our findings are in line with that of Odjegba (2012) and Singh et al (2015a) in Arabidopsis thaliana and Oryza sativa L. SA mediated lowering in ROS indicates a protective role against As-stress.…”
Section: Contamination Of As In Plants Has Closely Been Linkedsupporting
confidence: 92%
“…Arsenic-toxicity constitutes one of the major abiotic threats that not only disturb crop production instead human health also. Recent reports revealed that exogenous application of certain chemicals may result in the alleviation of various abiotic stresses that could be important from both theoretical and applied point of views (Namdjoyan and Kermanian, 2013;Singh et al, 2015a). Among such chemicals, SA is recently receiving increasing attention due to its involvement in the plant growth regulation and abiotic stress tolerance mechanism (Dong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Singh et al (2015) reported that exogenous application of SA reverted the growth, and oxidative stress caused by arsenic V (As V) and significantly decreased As translocation to the shoots. Then, the level of iron (Fe) in root and shoot was completely interrelated with the transcript level of transporters responsible for the accumulation of Fe, OsNRAMP5, and OsFRDL1, in both plant organs.…”
Section: Influence Of Sa On Transport Mechanisms Involved In CD Tolermentioning
confidence: 99%
“…Furthermore, Srivastava et al (2014) explained that down regulation of OsLsi2 was owed to minor As concentration in rice shoots in response to thiourea supplementation with As. OsLsi1 is primarily responsible for AsIII transport to root was not related to As uptake in roots (Singh et al, 2015;Armendariz et al, 2016). Otherwise, SA has been revealed to activate ABC transporters in Glycine max (Eichhorn et al, 2006).…”
Section: Influence Of Sa On Transport Mechanisms Involved In CD Tolermentioning
confidence: 99%